OUTCOME OF CONCOMITANT TREATMENT OF NON-CHRONIC TOTAL OCCLUSION LESION AT THE TIME OF CHRONIC TOTAL OCCLUSION INTERVENTION - Khan, Ali Nawaz; Ullah, Azmat; Saif, Mohsin; Shah, Noor; Samore, Naseer Ahmed; Pervaiz, Farrah; Kamran, Javeria; Bari, Fazal; Khan, Anusha; Khan, Aleena (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the outcome of concomitant treatment of a non-chronic total occlusion lesion at the time of chronic total occlusion intervention at AFIC-NIHD. Study Design: Observational study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases Rawalpindi, from Nov 2020 to Apr 2021. Methodology: A total of 171 patients presenting with chronic total coronary occlusion lesions were enrolled in study. Patients were randomized into two groups, group one with chronic total coronary occlusion only group and group two with combined group (chronic total coronary occlusion with non- chronic total coronary occlusion lesion) after coronary angiogram. The primary end-point assessed was angiographic (<30% residual diameter stenosis), clinical and procedural outcomes (TIMI grade flow, major adverse cardiac events (MACE) including death, stent thrombosis (ST), MI, repeated symptoms requiring repeat target vessel revascularization (TVR) either PCI or CABG, pericardial tamponade requiring pericardiocentesis or surgery and stroke) in patients with only chronic total coronary occlusion PCI group and combined group (chronic total coronary occlusion with non- chronic total coronary occlusion). Results: A total of 171 patients with chronic total coronary occlusion lesions were enrolled in the study. The mean age was 60.61 ± 9.68. There was no significant difference in perihospital complications, MACE in the two groups. However, there was increased contrast volume and radiation used in the combined group. Conclusion: Combined chronic total coronary occlusion and non- chronic total coronary occlusion lesion PCI can be done in a single procedural setting with acceptable complications and high success rate.